Stacking of purines in water: the role of dipolar interactions in caffeine - Tavagnacco, L.; Di Fonzo, S.; D’Amico, F.; Masciovecchio, C.; Brady, J. W.; Cesàro, A. (Physical chemistry chemical physics : PCCP, 2016)
During the last few decades it has been ascertained that base stacking is one of the major contributions stabilizing nucleic acid conformations. However, the understanding of the nature of the interactions involved in the stacking process remains under debate and it is a subject of theoretical and experimental studies. Structural similarity between purine bases (guanine and adenine) in DNA and the caffeine molecule makes caffeine an excellent model for the purine bases. The present study clearly shows that dipolar interactions play a fundamental role in determining stacking of purine molecules in solution. In order to reach this achievement, polarized ultraviolet Raman resonant scattering experiments have been carried out on caffeine aqueous solutions as a function of concentration and temperature. The investigation pointed out at the aggregation and solvation properties, particularly at elevated temperatures. Kubo–Anderson theory was used as a framework to investigate the non-coincidence effect (NCE) occurring in the totally symmetric breathing modes of the purine rings, and in the bending modes of the methyl groups of caffeine. The NCE concentration dependence shows that caffeine aggregation at 80 °C occurs by planar stacking of the hydrophobic faces. The data clearly indicate that dipolar interactions determine the reorientational motion of the molecules in solution and are the driving force for the stacking of caffeine. In parallel, the observed dephasing times imply a change in caffeine interactions as a function of temperature and concentration. A decrease, at low water content, of the dephasing time for the ring breathing vibration mode indicates that self-association alters the solvation structure that is detectable at low concentration. These results are in agreement with simulation predictions and serve as an important validation of the models used in those calculations.